Very long baseline interferometry properties of compact interplanetary scintillators detected by the Murchison Widefield Array. Issue 2 (20th October 2021) - Jaiswal, Sumit; An, Tao; Wang, Ailing; Tingay, Steven
ABSTRACT: Interplanetary scintillation (IPS) provides an approach for identifying the presence of subarcsec structures in radio sources, and very long baseline interferometry (VLBI) technique can help verify whether the IPS sources have fine structures on milliarcsec scales. We searched the available VLBI archive for the 244 IPS sources detected by the Murchison Widefield Array at 162 MHz and found 63 cross-matches. We analysed the VLBI data of the 63 sources and characterized the compactness index in terms of the ratio R of the VLBI-measured flux density at 4.3 GHz to the flux density estimated using the Very Large Array Sky Survey at 3 GHz and National Radio Astronomy Observatory NRAO Very Large Array Sky Survey at 1.4 GHz ( S VLBI / S SA ). A total of 11 sources are identified as blazars according to their flat spectra and strong variability. They show high compactness indices with R > 0.4, compact core-jet structure, and a broad distribution of normalized scintillation index (NSI). Other sources show diverse morphologies (compact core, core and one-sided jet, and core and two-sided jets), but there is a correlation between R and NSI with a correlation coefficient r = 0.47. A similar R –NSI correlation is found in sources showing single steep power law or convex spectra. After excluding blazars (which are already known to be compact sources) from the VLBI-detected IPS sources, a strong correlation is found between the compactness and scintillation index of the remaining samples, indicating that stronger scintillating sources are more compact. This pilot study shows that IPS offers a convenient method to identify compact radio sources without the need to invoke high-resolution imaging observations, which often require significant observational time.